Jakarta Abad XIX dalam Kolofon Naskah Melayu Koleksi A.B. Cohen Stuart di Perpusnas RI - Siti Deviyanti (Perpustakaan Nasional RI, 2022)
As a note written directly by the copyist/owner of the manuscript outside the text of the manuscript, the colophon can serve as a source of information about the history of its manuscript. Not only that, colophons can also function as a source of past knowledge outside the manuscript’s tradition. This is as shown by the colophons contained in the Malay manuscripts collection of A.B. Cohen Stuart stored in the National Library of Indonesia. This research on colophon manuscripts was carried out using descriptive methods and philological work steps to analyze data sources in the form of colophons. The results of the analysis, it can be concluded that 38 Malay manuscripts from the collection of Cohen Stuart are estimated to have been collected during his duty as conservator at Bataviaasch Genootschap, Batavia (Jakarta) in 1862-1871. These manuscripts were copied and/or owned by as many as 22 copyists/owners who lived in 16 villages in Jakarta in the period 1863-1869, except for two manuscripts which are estimated to be dated to the 1840s. Most of the manuscripts were copied for commercial purposes, i.e. for rent or sale. In addition, this colophon analysis also reveals some of the history of the city of Jakarta in the 19th century, including the structure of government, the villages in Batavia, as well as the formation of the Betawi ethnicity and the livelihoods of its people.